African pests and diseases - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Common African Pests and Diseases of Cassava, Yam, Sweet Potato and Cocoyam / Theberge, R.L.,1985. IITA. Ibadan, 108 pp ISBN 978 131 001 4